A dataset of scientific dates from archaeological sites in eastern Africa spanning 5000 BCE to 1800 CE - Iminjili, Victor; Crowther, Alison; Fisher, Michael T; Kay, Andrea; Roberts, Patrick; Goldstein, Steve; Boivin, Nicole; Fernandes, Ricardo (Scientific data, 2025)
Large collections of archaeological spatiotemporal data can reveal past cultural and demographic trends, land use strategies, and processes of environmental adaptation. Within Africa, archaeological Big Data can contribute to the study of the spread of agriculture, domesticated species, and specific artefacts and technologies, as well as their ecological impacts. Although reviews addressing these topics are available for different parts of the continent, existing mid-late Holocene archaeology datasets have yet to be compiled into a central, open-access, standardized informatic-oriented dataset. Here we present Wanyika, a dataset of scientific dates from archaeological sites in eastern Africa spanning almost 7 millennia, from ~5000 BCE to 1800 CE. This dataset compiles published scientific dates and associated botanical, faunal, iron, and ceramic finds from sites in Kenya, Tanzania, the Comoros Islands, and Madagascar. The records also include data for megafauna extinctions in Madagascar. We describe the spatiotemporal coverage of the dataset, how the data were collected, the structure of the dataset, and the applied quality control measures.
Keywords: archeologie; dějiny 18. století; History, 18th Century; Humans; lidé; History, Ancient; Africa, Eastern; dějiny starověku; Archaeology; východní Afrika